h y Ali Haggett. - Haggett, Ali.; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2015)
This book is open access under a CC BY license and explores the under-researched history of male mental illness from the mid-twentieth century. It argues that statistics suggesting women have been more vulnerable to depression and anxiety are misleading since they underplay a host of alternative presentations of 'distress' more common in men.
Keywords: History; History, Modern; Great Britain -- History; Social history; Psychotherapy; Sociology; Sex (Psychology).; Gender expression; Gender identity; History; History of Science; Social History; History of Britain and Ireland; Modern History; Psychotherapy; Gender Studies; Electronic books